Finansowe instrumenty wsparcia rozwoju przedsiębiorczości rewitalizowanych obszarów Krakowa z wykorzystaniem funduszy UE - Świerczewska-Pietras, Katarzyna (Przedsiębiorczość - Edukacja, 2010)
The paper aims at analyzing entrepreneurs’ possibilities of profiting from financial instruments supporting revitalization activities on degraded areas of Krakow. Taking into consideration the fact that the process of revitalization is visible on many planes, covering all spheres of urban functioning, such as social, infrastructural and planning sphere, as well as the sphere connected with the protection of the environment, the paper will attempt to present the sphere influencing the economic development providing financial support of entrepreneurship within the framework of revitalization activities. It is presumed in the work that the main supporting instruments include: Local Revitalization Programmes (LRP) developed within the framework of the Integrated Regional Development Operational Programme for 2004-2006 (IRDOP 2004-2006), Regional Operational Programmes for 2007-2013 (ROP 2007-2013), as well as JESSICA and JEREMIE financial instruments.